A partial order on the set of complex matrices with index one. Issue 1 (2nd January 2018) - Wang, Hongxing; Liu, Xiaoji
Abstract : In this paper, we use the well-known Löwner order and the core partial order to introduce a new partial order on the class of core matrices which is not dominated by any of the known matrix partial orders. We characterize, study its relations with the Löwner partial order under constraints, and exemplify its differences with other partial orders.